How Principals' Perceived Resource Needs and Job Demands Are Related to Their Dissatisfaction and Intention to Leave Their Schools During the COVID-19 Pandemic. (May 2022) - Kaufman, Julia H.; Diliberti, Melissa K.; Hamilton, Laura S.
School principals are facing greater challenges during the COVID-19 pandemic than they have ever faced, which has implications for whether they can conduct their work productively and remain in their jobs over the long term. This article draws on a unique, nationally representative, longitudinal panel of K–12 public school principals across the United States to examine principals' self-reported resource needs and job demands during the COVID-19 pandemic as well as how those resource needs and demands are related to principals' dissatisfaction and their intention to leave their job. Although principals' reported resource needs (which increased over time) and teacher shortages were consistently related to dissatisfaction and intention to leave, various other job demands were predictors of dissatisfaction but not the intention to leave. These results have several implications for supporting and retaining principals as well as the teachers they serve.